Estudo químico e biológico dos extratos hexânico e clorofórmico de folhas de Cheiloclinium cognatum (Miers) A.C.Sm. (Celastraceae) e avaliação do perfil de fragmentação de seus triterpenos friedelânicos por APCI-IT-TOF - Rafael Cesar Gonçalves Pereira (2016)
Phytochemical study of hexane and chloroform leaf extracts fromCheiloclinium cognatum resulted in the isolation of sixteen constituents. The isolation yielded three fatty compounds mixture of long chain hydrocarbons, mixture of fatty alcohols, and mixture of fatty acids , two acyclic isoprenoids squalene and guttapercha , one steroid -sitosterol , mixture of three fatty acid ursane triterpeneesters 3-palmitoyl-urs-12-ene, 3-stearoyl-urs-12-ene, and 3-eicosanoyl-urs-12-ene , seven known friedelane triterpenes 3-oxo-friedelane, 3-hydroxyfriedelane, 3-oxo-28-hydroxyfriedelane, 3-oxo-22-hydroxyfriedelane, 3,4-seco-friedelan-3-oic acid, 3-oxo-29-hydroxyfriedelane, 3,29-dihydroxyfriedelane , and two new friedelane triterpenes 3,28,29-trihydroxyfriedelane, and 1-oxo-3,29- dihydroxyfriedelane. The nine friedelanes isolated were subjected to MS and MS/MS analyses by APCI-IT-TOF in order to obtain relevant information for rapid and efficient identification and characterization of these compounds by mass spectrometry. It was observed that for all oxygen-containing functional groups, an invariable water molecule loss was observed during the fragmentation process. The study of biological activity consisted in the in vivo antiangiogenic assessment of friedelane triterpenes through the HET-CAM assay, and their nematicidal potential by the acute toxicity testing using the nematode Caenorhabditis elegans. In HET-CAM assay, all samples showed over 50% of vascular growth inhibition, displaying a great antiangiogenic potential associated to friedelane-type triterpenes. In the acute toxicity testing, three triterpenes exhibited mortality rate superior to 90%, giving prominenceto the compound 3-oxo-28-hydroxyfriedelane, which killed 100% of the larvae at concentration of 10 µg mL-1